Hypersensitivity pneumonia and HIV infection in occupational settings: a case report from northern Italy - Riccò, Matteo; Vignali, Alessandro; Pesci, Marco (Acta Biomedica Atenei Parmensis, 2019)
We describe a case of relapsing hypersensitivity pneumonitis (HP) manifesting as a reconstitution inflammatory syndrome (IRIS) in a HIV infected patient receiving antiretroviral therapy (HAART). The patient, who works as a farmer since the early 20s, was diagnosed with HP at age 23: after an initial steroid therapy, a long lasting clinical regression followed. At age 32, HIV positivity was diagnosed, with HAART starting only at age 38 (initially, lamivudine 300 mg/daily + zidovudine 300 mg b.i.d.). In the following 15 years, CD4+ count remained 600 cells/µL) with undetectable viral load then followed. Eventually, the patient developed cough and slowly worsening dyspnoea. Laboratory exams (serum T cell lymphocyte count 83%, CD8+ 45-51%; serum IgG for M faeni=78 mg/L and P notatum >200 mg/L) and high-resolution computer tomography (HRCT) were compatible with relapsing HP. The working tasks were modified avoiding any contact with allergens, then achieving a 6 months long clinical regression. Detectable HIV load (62 copies/mL) was identified at follow-up, and emtricitabine 200 mg/tenofovir disoproxil fumarate 245 mg s.i.d. was added to HAART. Respiratory involvement newly relapsed. HAART was shifted to emtricitabine 200 mg/tenofovir disoproxil fumarate 245 mg s.i.d. and raltegravir 400 mg b.i.d. Within several weeks, signs and symptoms resolved almost completely (peripheral oxygen saturation >95%: CD4+ count remained >600 cells/µL with CD8+ count steadily 55%).